Development of women and children in rural areas - Hemalatha Prasad, C. (New Delhi : Discovery Pub. House, 1996)
Case study of Haryana, Himachal Pradesh, Karnataka, and Pondicherry, India.
Includes bibliographical references (p. 125) and index.
Rashid
Keywords: Women in rural development -- India; Rural women -- India -- Social conditions; Rural children -- India -- Social conditions